2022
DOI: 10.5755/j02.ms.26796
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Evaluation of Diatomite Doped Fly Ash Based Geopolymers

Abstract: In this work, the properties of alkali silicate geopolymer type materials and diatomite as additive to fly coal ash was investigated using thermic coal plant’s fly ash in alkaline solution. The reacted products of alumino-silicate geopolymers using fly ash plus diatomite were pseudo-amorphous aluminosilicate gel and calcite and their mechanical and thermal properties were evaluated by the addition of diatomite. The compressive strength of this geopolymer is similar to that of the Portland cement mortar of PC20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
1
4
1
Order By: Relevance
“…The large amount of diatomite caused a higher reduction in compressive strength. A reduction in compressive strength as an effect of diatomite addition has been observed previously for geopolymers based on fly ash [12,16]. However, other investigation showed that diatomite addition increased mechanical properties [32].…”
Section: Mechanical Properties Of Compositesupporting
confidence: 64%
See 2 more Smart Citations
“…The large amount of diatomite caused a higher reduction in compressive strength. A reduction in compressive strength as an effect of diatomite addition has been observed previously for geopolymers based on fly ash [12,16]. However, other investigation showed that diatomite addition increased mechanical properties [32].…”
Section: Mechanical Properties Of Compositesupporting
confidence: 64%
“…been observed previously for geopolymers based on fly ash [12,16]. However, other investigation showed that diatomite addition increased mechanical properties [32].…”
Section: Mechanical Properties Of Compositementioning
confidence: 66%
See 1 more Smart Citation
“…Due to the numerous internal pores in geopolymer coatings, diatomite can act as a fine aggregate filler [ 48 ]. Initially, due to its higher water absorption, an increase in diatomite concentration results in higher adsorption of free water, thereby slowing down the progress of geopolymer hydration reactions [ 84 ]. This delay resulted in the surface hardness of the geopolymer coatings with added diatomite being lower than that of the blank group.…”
Section: Resultsmentioning
confidence: 99%
“…The bonding strength and surface hardness, crucial performance indicators for coatings, effectively reflect the protective effect of geopolymer coatings on concrete structures. The interfacial bonding between geopolymer coatings and concrete arises from physicochemical interactions at the contact surfaces between phases [43][44][45][46][47]. Figure 11a illustrates the bond strength of geopolymer coatings with varying diatomite concentrations at curing ages of 3 days, 7 days, and 28 days.…”
Section: Mechanical Properties Of Geopolymer Coatingsmentioning
confidence: 99%